Thermo-Convective Solution Growth of Vertically Aligned Zinc Oxide Nanowire Arrays for Piezoelectric Energy Harvesting - Frank Eric Boye Anang; Andam Deatama Refino; Gunilla Harm; Defang Li; Jiushuai Xu; Markys Cain; Uwe Brand; Zhi Li; Marion Görke; Georg Garnweitner; Erwin Peiner (Micromachines)
The search for a synthesis method to create longer ZnO NWAs with high-quality vertical alignment, and the investigation of their electrical properties, have become increasingly important. In this study, a hydrothermal method for growing vertically aligned arrays of ZnO nanowires (NWs) using localized heating was utilized. To produce longer NWs, the temperature environment of the growth system was optimized with a novel reaction container that provided improved thermal insulation. At a process temperature above ~90 °C, ZnO NWs reached a length of ~26.8 µm within 24 h, corresponding to a growth rate of 1.1 µm/h, nearly double the rate of 0.6 µm/h observed in traditional chemical bath growth using a glass reactor. The densely grown NWs (~1.9/µm2), with a diameter of ~0.65 µm, exhibited a preferred hexagonal c-axis orientation and were vertically aligned to the (100) silicon (Si) substrate. These NW structures have multiple applications, e.g., in piezotronic strain sensors, gas sensing, and piezoelectric energy harvesting. As proof of concept, a piezoelectric nanogenerator (PENG) was fabricated by embedding the NWs in an S1818 polymer matrix over a 15 mm × 15 mm area. Under repeated impulse-type compressive forces of 0.9 N, a maximum peak output voltage of ~95.9 mV was recorded, which is higher by a factor of four to five than the peak output voltage of 21.6 mV previously obtained with NWs measuring ~1.8 µm in length.